Study on Characteristic of Bed Material and Bed Load Discharge in Sungai Jemberau, Tasik Chini - Nadiatul Adilah, Ahmad Abdul Ghani; N. Syamimi, Namin; Norashikin, A. Kamal; Duratul Ain, Tholibon; Junaidah, Ariffin (Akademi Sains Malaysia, 2018)
Tasik Chini is located in the state of Pahang about 100 km from Kuantan, the capital of the state of Pahang. Most of the lowland within the study area has been converted into agricultural and including rubber and oil palm plantations and mixed crops. This logging and mining activities gave impact to sediment characteristics and discharge. The purpose of this study was to identify the bed material characteristics and to determine the bed load discharge in Sungai Jemberau at Tasik Chini. Bed material sample was collect at Sungai Jemberau in 24 November 2016, 1 December 2016 and 5 March 2017. Bedload discharge also measured between these date. The bed load discharges also estimate by using Duboys and Schoklitschequation to identify the suitable predicted method for this area. From the analysis of the results, DuboysEquation was more suitable to predict and estimate the bed load discharges for Sungai Jemberau at Tasik Chini because the predicted value closer to measured value.